Aplicação do modelo Epstein-Wilmot ao mercado brasileiro - Silva, Gustavo Gonçalves Rodrigues da (2021)
This dissertation focuses on the Epstein-Wilmott model, which is considered an uncertain interest rate model. Differently from the others interest rate models studied in the literature so far, this one has a non-probabilistic approach. The model is applied here by using Brazilian market data, where the CDI is used as the short rate. The concept of the model is to price a portfolio considering the worst possible path of the short rate and guaranteeing a result with no losses if it occurs. The model’s validation was confirmed, as the exemplification of the pricing of a ZCB and also of a CDI indexed derivative. Besides the implementation and validation of the model two backtests were done, where in the first one the model is used to test arbitrage with futures DI contracts. In the second backtest, different indexes of the CDI are priced and its final hedged portfolio is simulated. In general, the model seems consistent and easy to parameterize, but there were also negative results in the backtests due to the violation of one of the parameters that restrict the CDI evolution.